Aktivitas antibakteri Moringa oleifera Lam. terhadap bakteri patogen resisten antibiotik - Herlina Rante; Burhanuddin Taebe; Cahyani Purnasari; Christiana Lethe (Jurnal Farmasi dan Ilmu Pengobatan, 2017)
A research on the antimicrobial activity assay of leaf extract of Moringa (Moringa oleifera Lam.) by disk diffusion method then continued to TLC-bioautography has been done. Moringa leaves macerated using ethanol 70%. The antimicrobial activity on Escherichia coli and Staphylococcus aureus which was resistant to antibiotics cultured Mueller Hinton Agar by agar diffusion method. The results showed that moringa leaf extract began to inhibit the growth of S. aureus and E. coli at a concentration 100 mg/mL (d= 6.80 mm) and 50 mg/mL (9.20 mm). Identification of common compounds by TLC showed the extract contain alkaloids, steroids, terpenes, phenolics, and flavonoids, and terpenoid active in TLC-bioautography.